Solar Wind Deflection by Mass Loading in the Martian Magnetosheath Based on MAVEN Observations - E. Dubinin; M. Fraenz; M. Pätzold; J. S. Halekas; J. Mcfadden; J. E. P. Connerney; B. M. Jakosky; O. Vaisberg; L. Zelenyi (Geophysical Research Letters, 2018)
Abstract Mars Atmosphere and Volatile EvolutioN observations at Mars show clear signatures of the shocked solar wind interaction with the extended oxygen atmosphere and hot corona displayed in a lateral deflection of the magnetosheath flow in the direction opposite to the direction of the solar wind motional electric field. The value of the velocity deflection reaches ∼50 km/s. The occurrence of such deflection is caused by the “Lorentz‐type” force due to a differential streaming of the solar wind protons and oxygen ions originating from the extended oxygen corona. The value of the total deceleration of the magnetosheath flow due to mass loading is estimated as ∼40 km/s.